Pemetaan Area Risiko Sanitasi Sektor Air Limbah Domestik Kota Cimahi - Heksantia Rahmadinda Yasya; Iwan Juwana (Jurnal Serambi Engineering, 2019)
Cimahi is one of developing cities in Indonesia that has sanitation condition with low services, especially in domestic wastewater management. In 2016, the coverage of domestic wastewater services in the city only reached 68.17%. In consequences, some communities discharging their wastewater to the stream. This matter could lead to water pollution that would indirectly affecting public health. Based on these problems, this reserach was carried out to calculate the level of risk in each urban village of Cimahi. The risk level is stated in the form of scores (1-4) with a description of 1 is very low risk; 2 is low risk; 3 is high risk; 4 very high risk. The risk calculation considers the determinants (exposure and impact) which consist of  percentage of wastewater service, risk index, perceptions of related regional organizations, population, population density, poverty rates, and regional categories. The results obtained from the calculation of the risk of domestic wastewater in Cimahi show that the Pasirkaliki, Cibabat, Citeureup, Cipageran, Baros, and Cibeber have a very low risk; Cimahi and Utama are at low risk; Karangmekar, Cigugur Tengah and Cibeureum are at high risk; Padasuka, Setiamanah, Leuwigajah and Melong have a very high risk.